Heavy Metal Accumulation in Paddy Fields Along the Trans Sumatra Toll Road, MKTT Section - Fernando, Josua Puji Lois; Sahfitra, Angga Ade; Desimember P, Jesika Esra; Dalimunthe, Nur Asyiah; Rannando, Rannando (Jurnal Biologi Tropis, 2024)
The aim of this research is to determine whether there is an accumulation of heavy metals in lowland rice fields cultivated along the MKTT Trans Sumatra toll road and to find out the factors that influence the distribution of heavy metals in lowland rice fields along the MKTT toll road. The method used in the research is quantitative descriptive method. After averaging the heavy metals Lead (Pb), Cadmium (Cd) from the three sampling locations, the highest level of PB or lead metal was 0.0000618251ppm, while the highest level of Cadmium (Cd) was 0.000007234ppm, based on this it can be It can be concluded that the highest metal content is in Lead (Pb), namely 0.0000618251ppm. Based on this data, it can be concluded that plants or crops located near the roadside have the potential to be contaminated or contaminated with heavy metals due to nearby transportation activities which produce emissions, etc. and other factors. from the use of fertilizers and pesticides used by farmers.